Dampak Kebijakan Pemulihan Ekonomi Terhadap Usaha Mikro Kecil Menengah (UMKM) Pasca Covid-19 - Nasution, Askur Hamid; Saragih, Arif Kusnedi; Lestari, Dini (Yayasan Pendidikan Islam Akmalia, 2022)
This study aims to determine the Impact of the Dendang Sea Village Government Policy on the Economic Recovery of Culinary MSMEs in the Dendang Sea area after Covid-19. This research is a qualitative research using descriptive methods and P ustaka studies. The process of retrieving and collecting data by survey method and through library method. The data presented in this study are data obtained from field studies, literature searches from books, official government websites, official reports from international organizations, official news websites, and data processed from other relevant sources. From the data described above, it can be concluded that the increase in the Income of Traditional Traders in the Dendang Sea Area During the Covid-19 Pandemic has made major changes to traditional traders in the traditional market of Lau Dandang, both those who use their own shophouses and those who rent places. The change is in the form of income levels that have decreased by almost 30% from before the covid-19 outbreak, from the covid-19 pandemic, to now after the covid-19 pandemic, the income level has increased by almost 40%.